2023
DOI: 10.3389/fphys.2022.1082174
|View full text |Cite
|
Sign up to set email alerts
|

Relative age effects in track-and-field: Identification and performance rebalancing

Abstract: Introduction: Relative Age Effect (RAE) consists of a biased distribution of the dates of birth in a same-age group.Objectives: This study aimed to investigate Relative Age Effect among French athletes in different track-and-field events, and propose a corrective adjustment method to highlight the true potential of an athlete with respect to his/her relative age.Methods: 358,610 performances from 2009 to 2019 of female and male athletes between 12 and 21 years old were collected. Relative age distributions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…It was demonstrated that the RAE decreased with age, but the effect was still present in the senior age group in both male and female athletes ( Kirkeberg et al, 2022 ). Another large study involving French track and field athletes of different ages revealed the presence of the RAE, which increased with the level of competitiveness ( Difernand et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the RAE decreased with age, but the effect was still present in the senior age group in both male and female athletes ( Kirkeberg et al, 2022 ). Another large study involving French track and field athletes of different ages revealed the presence of the RAE, which increased with the level of competitiveness ( Difernand et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%